Ultrafast Water Permeation in Graphene Nanostructures Anomalously Enhances Two‐Phase Heat Transfer. Issue 13 (16th May 2018) - Tong, Wei Li; Hung, Yew Mun; Yu, Hao; Tan, Ming Kwang; Ng, Boon Thiam; Tan, Boon Thong; Wu, Heng An; Soh, Ai Kah
Abstract: The unique property of ultrafast water transport in graphene nanoplatelets (GNPs) coating is attributed to the frictionless interaction between the smooth hydrophobic carbon nanostructures and the well‐ordered hydrogen bonds of water molecules, whereas the driving force originates from the randomly distributed hydrophilic functionalities. The anomalous two‐phase heat transfer enhancement that results from this distinctive property of GNPs‐coating is investigated. The fast water permeation property of graphene enables the formation of ultrathin water film that synergizes the evaporation and the circulation of water in a two‐phase closed thermosyphon (TPCT). In addition, the GNPs‐coating which performs as a hydrophilic surface, improves the droplet nucleation during condensation and its fast water permeation property augments the circulation of condensate back to the evaporator. Ultimately, the ultrafast water permeation property of GNPs‐coating enhances the efficiencies of all the three main processes taking place in a TPCT, namely, evaporation, condensation, and circulation of condensate, leading to a maximum enhancement of 80.7% in the effective thermal conductance and 116.3% in the evaporative heat transfer coefficient. The experimental results are supported by the molecular dynamics simulations. A great potential for the application of GNPs‐coating in the phase‐change heat transfer devices is envisaged. Abstract : The unique property of ultrafast water transport in graphene nanoplatelets (GNPs) coating enables the formation of ultrathin water film that enhances the evaporation, condensation, and circulation of condensate in a two‐phase closed thermosyphon (TPCT). Ultimately, the GNPs‐coating augments all the three main processes taking place in a TPCT, leading to a drastic increase in the overall performance.